Understanding nitrogen dynamics in the Brazilian beef industry: A comprehensive decadal analysis - Rezende, Vanessa Theodoro; Nacimento, Rafael Araújo; Ali, Sher; Rodrigues, Gustavo Roberto Dias [UNESP]; Romanelli, Thiago Libório; Cyrillo, Joslaine Noely dos Santos Gonçalves; Bonaudo, Thierry; Lescoat, Philippe; Gameiro, Augusto Hauber (Elsevier, 2024)
Brazil stands as a prominent beef producer and exporter, witnessing major transformations and expansions in its production chain over the past 20 years. These changes have prompted concerns regarding waste generation and environmental pressure. This study employs material flow analysis (MFA) to quantify nitrogen flows throughout the cattle slaughter process and subsequent beef consumption in Brazil, spanning from 2011 to 2021. The analysis encompasses co-production streams like leather, tallow, viscera, and blood. Nitrogen use efficiency (NUE) and the nitrogen cascade indicator (NCI) were used to evaluate efficiency and nitrogen accumulation in the production chain. Nitrogen inputs in the system increased by 8.47 %, while beef production rose by 7.29 %. In contrast, per capita beef consumption decreased by 1.29 kg, despite an overall consumption increase of 2.84 %, attributed to population growth in Brazil. Beef exports witnessed a notable surge of 86.03 %. Conversely, human excreta and food waste losses experienced increments of 10.88 % and 2.84 %, respectively. Examining NUE reveals the highest values during the slaughter phase (90 %), followed by processing, transportation, and storage stages (79–88 %). The consumption phase exhibited the lowest NUE values (29–34 %). Regarding the cumulative nitrogen effect, the NCI varied between 77 % and 82 % throughout the study period. This highlights opportunities for enhancing nitrogen use efficiency, particularly by addressing food waste at the consumer level. Notably, the study observes nitrogen accumulation across the Brazilian beef production chain, potentially contributing to the nitrogen cascade effect and heightening environmental pressure. Recognizing these dynamics provides avenues for targeted improvements, emphasizing the need to address nitrogen-related challenges and enhance sustainability in the beef production and consumption landscape.
Keywords: Agroindustry; Manure; Material flow analysis; Nutrients; Slaughterhouse